Unveiling the Divine Tapestry: A Comparative Analysis of the Devarāja Cult and the European Divine-Right Theory - Rahman, Puteh Noraihan A (Journal of Ecohumanism, 2024)
The concept of kingship has a long history, predating recorded history and likely emerging alongside the desire for communal leadership. Political scientists and historians have consistently explored the development of leadership, political, and governance skills in the context of early societies. While the core principles of serving a king have varied across cultures based on communal needs, many have been intertwined with religious and supernatural beliefs. This paper aims to analyze the contrasting notions of kingship held by medieval Europeans and Malays, specifically focusing on the concept of divine right and the associated authority vested in the kingship. This study embarks on a multifaceted exploration of the concept of the divine king, delving into its manifestations within European and Malay societies. The primary objective is to illuminate distinct characteristics that shaped this ideology in these contrasting cultural landscapes. By meticulously dissecting the defining features of the divine king in each civilization, this study aims to shed light on the unique ways in which this belief system legitimized and bolstered royal authority Secondly, the investigation will delve into the far-reaching consequences of the belief in the divine right of kings. An exploration on how far the ideology was permeated various aspects of European and Malay societies, influencing not only political structures but also social order, legal frameworks, and even artistic expressions. By examining the extent of this impact, we can gain a deeper understanding of how the concept of the divine king shaped the historical trajectories of these civilizations, Finally, the study will turn its focus specifically to the "devarāja " cult, a cornerstone of Malay political and religious thought. This unique belief system, serving as a tangible manifestation of the Malay concept of divine kingship, will be meticulously analyzed. This research dissected rituals, symbols, and underlying philosophies associated with the devarāja cult, drawing comparisons and contrasts with the European model of divine right. By unraveling the intricacies of the devarāja, we can gain valuable insights into the Malays’ distinctive approach to legitimizing and venerating their rulers.Through this comprehensive comparative analysis, we aim to not only illuminate the common threads that bind the European and Malay concepts of the divine king but also to celebrate the unique tapestry woven by each civilization. This exploration promises to enrich our understanding of the multifaceted ways in which societies have historically constructed and justified absolute power.This study will utilize a comparative historical approach to dissect the concept of the divine king in both medieval Europe and the Malay world. To achieve this, three key objectives will guide the research. First, we aim to identify the distinct characteristics of the divine-king concept within each region. This will involve analyzing literary sources such as European medieval chronicles and related texts which discussing about religion and states particularly on consolidating monarch’s political power through divine-king concept. For the Malay perspective, literary manuscripts such as Hikayat Banjar, Hikayat Panji Semirang, Sulalatul-Salatin (Malay Annals), Misa Melayu, Hikayat Sang Boma and descriptions of devarāja rituals through scholarly writing by Coedès, G., Aymonier, E., and Mabbet, I. W. will be scrutinized. he objective of this article is to analyze the concept of the divine king. It foreshadows that the analysis will be based on scholarly works to provide a well-rounded understanding grounded in established research. To achieve this, analyzing the history of medieval European political thought and the development of the divine right theory is crucial. For the Malay world, research will delve into the history of Malay kingdoms and the evolution of the devarāja concept. The study will then move beyond identifying the concept to explore its practical implications. A comparative analysis will be conducted to understand how the belief in divine right impacted both societies. This will involve examining how it solidified the monarch’s political power, legitimized their decisions, and shaped their relationships with other power structures. In Europe, this might involve analyzing the influence on the Church, while in the Malay world, the focus would be on monarchial institutions. Furthermore, the research will delve into how divine right impacted the social order, including societal structures, the concept of obedience to the ruler, and the king’s perceived role as a moral compass. Finally, the analysis will explore how the belief in divine right justified military campaigns and expansionist policies. To understand the devarāja cult specifically within the Malay world, the study will utilize primary sources documenting the rituals associated with it. These may include descriptions of ceremonies, inscriptions related to specific practices, and accounts of offerings or regalia used in the rituals. Scholarly works on the devarāja concept, its rituals, and its significance within Malay society will also be consulted. If feasible, the research may be further enriched by incorporating interviews with cultural experts or religious figures to gain insights into how the devarāja legacy is understood in the contemporary Malay world.In order to uncover important ideas from the information we collect, this study will use two different analysis methods. The first method, thematic analysis, will help us find repeated ideas and patterns within the data. This will allow for a deeper understanding of the core characteristics of the divine-king concept in both Europe and the Malay world. Secondly, comparative analysis will be employed to highlight similarities and differences between these two regional interpretations. This comparative approach is crucial for revealing the unique nuances of each concept and fostering a more comprehensive understanding of the divine king across cultures. However, it is important to acknowledge potential limitations. The availability of primary sources, particularly for the devarāja cult in the Malay world, may be limited. On the whole, this research sheds light on the distinct characteristics of divine kingship across cultures. While Western and Malay societies both embraced the concept, their interpretations differed. The Malays, in particular, developed the elaborate devarāja cult, a system of rituals reinforcing their king’s divine status. Although the study focuses on the Frankish empire and Malay kingship, it opens a door to understanding the unique ways both civilizations blended secular and spiritual authority within their monarchies. This exploration is valuable for researchers in political science, social history, cultural anthropology, and socio-psychology, offering initial insights into how communities viewed and interacted with their monarchs.